Role of serotonin in modulation of decision-making in Parkinson's disease. (April 2023) - Nobis, Lisa; Maio, Maria Raquel; Saleh, Youssuf; Manohar, Sanjay; Kienast, Annika; McGann, Emily; Husain, Masud
Background: Dysfunction of dopaminergic pathways has been considered to play a pivotal role in Parkinson's disease (PD), affecting the processing of emotional and rewarding information, and potentially leading to symptoms of depression or apathy. However, some aspects of motivation in PD might be affected by non-dopaminergic mechanisms. Aim and method: The objective of this experimental medicine study was to investigate the contribution of serotonergic modulation via administration of citalopram (20 mg) for 7 days on motivated decision-making in twenty PD patients, measured using several different computerised tasks and clinical questionnaires that probe different aspects of decision-making. Twenty healthy controls were additionally tested without medication to assess any baseline differences between the two groups. Results: Results indicated that PD patients were overall less motivated than controls on an effort- and reward-based decision-making task. Citalopram increased or decreased willingness to exert effort for reward, depending on whether baseline motivation was high or low, respectively. A task assessing decision-making under risk revealed higher levels of risk aversion for potential losses in PD patients, which neither serotonin nor the patient's regular dopaminergic medication seemed to restore. However, citalopram in PD was associated with more risk-seeking choices for gains, although patients and controls did not differ on this at baseline. Conclusion: The results provide evidence for a role of the serotonergic system in influencing some aspects of motivated decision-making in PD processes.